Pengaruh efektivitas dewan komisaris efektivitas komite audit kepemilikan keluarga dan kepemilikan Institusional, terhadap biaya ekuitas pada Perusahaan manufaktur yang terdaftar Di BEI tahun 2011. - Wahyu Sidiq Anwar Syahbudin (AKT 13 UMY 229, 2013)
This study aims to analyze the effect of family ownership, institutional ownership, effective comisionaris board, effective audit comitte on cost of equity in manufacturing companies listed in BEI in 2012. The subject inthis study was annual report manufacturing companies listed in BEI in 2012. In study, sample 96 annual reports were selected using purposive sampling. Analyisis tools used in this study is the Multiple Regression. Based on the analysis that have been made the result are family ownership significantly influence on cost of equity. But institutional ownership, effective comisionaris board and effective audit commite are no significantly influence. Keywords : family ownership, institutional ownership, effective comisionaris board, effective audit comitte, cost of equity.